Constraints in Commercial Banana Cultivation - K.G.Sangeetha; Mothilal Nehru (Journal of Agricultural Extension Management, 2025)
Banana is one of the important commercial tropical crops in India. This study carried out in Thiruvananthapuram district of Kerala, identifies and analyzes constraints in commercial banana cultivation as perceived by the growers, as a part of formulating an extension strategy for improving commercial banana cultivation. The results reveal production constraints including incidence of pests and diseases followed by labour scarcity while economic constraints include high cost of inputs, high labour charges, price fluctuation, inadequate credit and marketing facilities, high transportation charges etc. The study suggests that, most of the production and economic constraints can be addressed by promoting group farming, farmer’s consortium, decentralized planning and building market linkages to make banana cultivation a profitable enterprise. Banana fruit known as the poor man’s apple is an item of food consumed from the lowest hut to the royal palace. It is one of the most important commercial tropical crops in India. The scope of banana processing and exporting is high enough to improve our economy through foreign exchange and employment generation. However, its potential to be grown as a commercial cash crop has not been exploited so far in Kerala. Hence, it is necessary to look into the factors limiting the cultivation and marketing of banana to tackle this crisis. Delineation of constraints in adopting the recommended technologies would help the research and extension system to strengthen the efforts and bridge the gap between technology transfer and adoption (Trivedi et al. 2008). Thus a study was conducted to identify and analyze the constraints in commercial banana cultivation as perceived by the growers as a part of formulating an extension strategy for improving commercial banana cultivation